2017
DOI: 10.5194/amt-10-1665-2017
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution mapping of the NO<sub>2</sub> spatial distribution over Belgian urban areas based on airborne APEX remote sensing

Abstract: Abstract. We present retrieval results of tropospheric nitrogen dioxide (NO 2 ) vertical column densities (VCDs), mapped at high spatial resolution over three Belgian cities, based on the DOAS analysis of Airborne Prism EXperiment (APEX) observations. APEX, developed by a Swiss-Belgian consortium on behalf of ESA (European Space Agency), is a pushbroom hyperspectral imager characterised by a high spatial resolution and high spectral performance. APEX data have been acquired under clear-sky conditions over the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 61 publications
8
56
0
Order By: Relevance
“…Previous studies indicate that the two main uncertainty sources for nadir observations of the NO 2 column are the ground albedo and the relative position of the NO 2 and aerosol layer (Leitão et al, 2010;Meier et al, 2017;Tack et al, 2017). In our case, the lidar and sonde indicate that the NO 2 and aerosols have a similar profile, as can be expected considering the large source in a rural area.…”
Section: Vertical Columns Of Nosupporting
confidence: 69%
See 1 more Smart Citation
“…Previous studies indicate that the two main uncertainty sources for nadir observations of the NO 2 column are the ground albedo and the relative position of the NO 2 and aerosol layer (Leitão et al, 2010;Meier et al, 2017;Tack et al, 2017). In our case, the lidar and sonde indicate that the NO 2 and aerosols have a similar profile, as can be expected considering the large source in a rural area.…”
Section: Vertical Columns Of Nosupporting
confidence: 69%
“…Regarding the atmospheric horizontal distribution, a growing interest appeared in the last decade for nadir-looking airborne DOAS instruments able to map trace gases below the aircraft. Maps of tropospheric NO 2 were acquired around power plants in South Africa (Heue et al, 2008) and in Germany (Schönhardt et al, 2015), or above urban areas like Houston (Kowalewski and Janz, 2009;Nowlan et al, 2016), Zurich (Popp et al, 2012), Indianapolis (General et al, 2014), Brussels and Antwerp (Tack et al, 2017), Leicester (Lawrence et al, 2015), and Bucharest (Meier et al, 2017). General et al (2014) also quantified NO 2 in the vicinity of the Prudhoe Bay oil field in Alaska.…”
Section: Introductionmentioning
confidence: 99%
“…Similar instruments have also been developed by other countries. In the last decade, airborne spectrometers have mapped high-resolution NO 2 in parts of Europe (Popp et al, 2012;Schönhardt et al 2015;Lawrence et al, 2015;Meier et al, 2017;Tack et al, 2017Tack et al, , 2019, the United States (Nowlan et al, 2016Lamsal et al, 2017;Judd et al, 2018), Asia , and Africa (Broccardo et al, 2018). Results from these efforts have illustrated the capability of airborne spectrometers to observe the impact of emission sources and meteorology on the spatial distribution of NO 2 (Popp et al, 2012;Schönhardt et al, 2015;Judd et al, 2018, andTack et al, 2019) and have shown utility for evaluating NO x emissions (Schönhardt et al, 2015;Souri et al, 2018) as these high-resolution measurements can resolve detailed NO 2 spatial patterns that satellites, at their current spatial resolutions, cannot (Broccardo et al, 2018;Lamsal et al, 2017;Judd et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…NO 2 amounts over industrial regions and urban areas have been mapped at high spatial resolution by several recently developed airborne push-broom sensors (Heue et al, 2008;Popp et al, 2012;Schönhardt et al, 2015;Lawrence et al, 2015;Nowlan et al, 2016;Meier et al, 2017;Tack et al, 2017Tack et al, , 2018Vlemmix et al, 2017;Broccardo et al, 2018). Airborne remote-sensing CH 2 O measurements have previously been made from aircraft using limb-viewing geometry by airborne multi-axis differential optical absorption spectroscopy (AMAX-DOAS) (Baidar et al, 2013) and by the whisk-broom scanning technique (where the cross-track spatial dimension is provided by mechanical scanning) using the Airborne Compact Atmospheric Mapper (ACAM) (Liu et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%